Solve for \( y \). \[ 6(y-2)=2 y-40 \] Simplify your answer as much as possible. \( y=\square \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To solve for \( y \), let's start by distributing the left side of the equation: \[ 6(y - 2) = 2y - 40 \] This gives us: \[ 6y - 12 = 2y - 40 \] Next, we need to get all the \( y \) terms on one side and the constants on the other. Subtract \( 2y \) from both sides: \[ 6y - 2y - 12 = -40 \] This simplifies to: \[ 4y - 12 = -40 \] Now, add 12 to both sides: \[ 4y = -40 + 12 \] Which simplifies to: \[ 4y = -28 \] Finally, divide both sides by 4: \[ y = \frac{-28}{4} \] This gives us: \[ y = -7 \] So the final answer is: \( y = -7 \)